Produção e purificação de L (+) ácido lático por Lactobacillus rhammosus utilizando processo de batelada alimentada - Bernardo, Marcela Piassi [UNESP] (2014)
This work presents study of production of L(+) lactic acid by Lactobacillus rhamnosus B 103 using different fermentative strategies with the aim of increase the production by fed batch fermentation. The study about the purification process of the lactic acid was also made. Optimized medium used was essentially composed of agribusiness residues: 60,00 g/L of lactose from whey (90,00 g/L of total reducing sugars), 45,00 mL/L of corn steep liquor, 1,00 mL/L of Tween 80 and 0,075 g/L of manganese sulfate. Four different kinds of batch fermentation were made: simple batch, constant feed rate fedbatch, pulse fed-batch and pH stat. The kinetic parameters of production and productivity were investigated during this study too. The best fermentation was the pH stat with feed medium containing only whey and corn steep liquor. The production was 143,70 g/L and the productivity for lactic acid in 24, 48 and 96 hours were 2,70; 2,25 and 1,49 g/L/h respectively. For the batch process the production was 57,00 g/L, for pulse fed-batch was 98,90 g/L and for constant feed fed-batch was 80,45 g/L. For extraction and purification of lactic acid different process were studied too: activated carbon, ion exchange, ultrafiltration, nanofiltration and vacuum filtration using activated carbon and celite. The double vacuum filtration using activated carbon and celite was the best process with recovery of lactic acid of 71%, lactic acid and reducing sugars relation of 0,5% and 100% of protein remotion